# 4_Inverse Trigonometic Functions.pdf

September 25, 2017 | Author: thinkiit | Category: Function (Mathematics), Sine, Analysis, Trigonometry, Complex Analysis

#### Description

1

INVERSE TRIGONOMETIC

INVERSE TRIGONOMETRIC FUNCTIONS 2.1.

INTRODUCTION We have read about functions, one-one onto (bijective) functions and inverse of a function. We have also learnt that inverse of a function f is denoted by f–1 and f–1 exists if and only if f is a one-one onto function. There are several functions which are not one-one onto and hence their inverse does not exist. We have also read about trigonometric functions are not one-one onto over their natural domains and ranges and hence their, inverse do not exist. But if we restrict their domains and ranges, then they will become one-one onto functions and their inverse will exist. In this chapter we will study inverses of trigomometric functions and their various properties.

2.2.

INVERSE OF A FUNCTION Let f : A ® B If (be a function from A to B) which is one-one onto. Then a function f–1 : B ® A (f–1 from B to A) is said to be the inverse of the function f if y = f(x) Û f–1(y) = x i.e., image of x under f is y Û image of y under f–1 is x. Clearly domain f–1 = range f and

range f–1 = domain f

2.3.

PRINCIPAL BRANCHES OF INVERSE TRIGONOMETRIC FUNCTIONS

(i)

Definition of sin–1 x (Principal branch of sin–1 x) : é p pù

p p

é ù sin–1 : [–1, 1] ® ê- , ú i.e., sin–1 is a function from [–1, 1] to ê- 2 , 2 ú . ë û ë 2 2û

(ii)

Such that

sin–1 x = q Û x = sin q

where

–1 £ x £ 1 and –

p 2

£q<

p 2

Definition of cos–1 x (Principal branch of cos–1 x) : cos–1 : [–1, 1] ® [0, p] is such that cos–1 x = q Û x = cos q, where –1 £ x £ 1 and 0 £ q £ p

(iii)

Definition of tan–1 x (Principal branch of tan–1 x) : æ

p pö

tan–1 : (–¥, ¥) ® ç - 2 , 2 ÷ such that è ø tan–1 x = q Û x = tan q where –¥ < x < ¥ and –

p 2

0 and xy < -1

Property VIII :

sin–1 x + sin–1 y =

ì sin -1{ x 1 - y 2 + y 1 - x 2 } , ï ï ï í p - sin -1 { x 1 - y 2 + y 1 - x 2 } , ï ï -1 2 2 ï - p - sin { x 1 - y + y 1 - x } , î

if - 1 £ x, y £ 1 and x 2 + y 2 £ 1 or if xy < 0 and x 2 + y 2 > 1 if 0 < x, y £ 1 and x 2 + y 2 > 1 if - 1 £ x, y < 0 and x 2 + y 2 > 1

www.thinkiit.in

7

INVERSE TRIGONOMETIC Property IX :

sin–1 x – sin–1 y =

ì -1 2 2 ï sin { x 1 - y - y 1 - x } , ï ï -1 2 2 í p - sin { x 1 - y - y 1 - x } , ï -1 2 2 ï - p - sin { x 1 - y - y 1 - x } , ï î

if - 1 £ x, y £ 1 and x 2 + y 2 £ 1 or if xy < 0 and x 2 + y 2 > 1 if 0 < x £ 1, - 1 £ y £ 0 and x 2 + y 2 > 1 if - 1 £ x < 0, 0 < y £ 1 and x 2 + y 2 > 1

Property X :

cos–1 x + cos–1 y =

ì 2 2ö -1 æ if - 1 £ x, y £ 1 and x + y ³ 0 ïïcos çè xy - 1 - x 1 - y ÷ø , í ï 2p - cos -1 æç xy - 1 - x 2 1 - y 2 ö÷ , if - 1 £ x, y £ 1 and x + y £ 0 ïî è ø

Property XI : ìcos -1 { xy + 1 - x 2 1 - y 2 } , ï

cos–1 x – cos–1 y = í

ïî - cos -1 { xy + 1 - x 2

if - 1 £ x, y £ 1 and x £ y

1 - y 2 } , if - 1 £ y £ 0, 0 < x £ 1 and x ³ y

This result can be established in the same way as in property X. Property XII :

(i)

2 tan–1 x =

ì æ 2x ö tan -1 çç ï ÷÷ , if - 1 < x < 1 è 1 - x2 ø ï ï -1 æ 2x ö ÷÷ , if x > 1 í p + tan çç è 1 - x2 ø ï ï -1 æ 2x ö ï- p + tan çç ÷÷ , if x < -1 è 1- x2 ø î

Property XIII :

(i)

(ii)

2 tan–1 x =

ì æ 2x ö sin -1 çç ÷÷ , if - 1 £ x £ 1 ï è 1+ x2 ø ï ï -1 æ 2x ö ÷÷ , if x > 1 í p - sin çç è 1+ x2 ø ï ï -1 æ 2x ö ÷÷ , if x < -1 ï - p - sin çç è 1+ x 2 ø î

2 tan–1 x =

ì æ 1 - x2 ö ÷ , if 0 £ x < ¥ ï cos -1 ç ç 1 + x2 ÷ ï è ø í 2ö æ ï -1 ç 1 - x ÷ , if - ¥ < x £ 0 ï- cos ç 2÷ è 1+ x ø î

www.thinkiit.in

8

INVERSE TRIGONOMETIC Property XIV :

x

(i)

sin–1 x = cos–1 1- x 2 = tan–1 1 - x2 æ

1

æ ç

1

ö ÷ 2 ÷ 1 x è ø

2 ç = cot–1 1 - x = sec–1 ç

x

Where x ³ 0 (ii)

æ 2 ç 1- x x è

cos–1 x = sin–1 1- x 2 = tan–1 çç æ ç

ö ÷

x

ö ÷ ÷÷ ø

1

ö ÷

–1 = cot–1 ç = cosec–1 ç 2 ÷ = sec 2 ÷ x è 1- x ø è 1- x ø

Where x > 0

(iii)

æ ç

x

–1

æ 1ö ç ÷ èxø

æ ç

ö ÷

1

ö ÷

–1 tan–1 x = sin–1 ç 2 ÷ = cos ç 2 ÷ è 1+ x ø è 1+ x ø

= cot

= sec

–1

1+ x

= cosec

2

–1

æ 2 ç 1+ x çç x è

ö ÷ ÷÷ ø

Property XV :

(i)

2 sin x = –1

ì -1 1 2 £x£ if ïsin ( 2x 1 - x ), 2 ï 1 ï -1 2 £ x £1 í p - sin (2x 1 - x ), if 2 ï ï 2 ï - p - sin (2x 1 - x ), if - 1 £ x £ î

1 2 1 2

Property XVI : (i)

ìï cos -1(2x 2 - 1) , if 0 £ x £ 1 ïî2p - cos -1(2x 2 - 1) , if - 1 £ x £ 0

2 cos–1 x = í

Property XVII :

3 sin–1 x =

ì sin -1(3 x - 4 x 3 ) , ï ïï -1 3 í p - sin (3x - 4x ) , ï ï - p - sin -1(3 x - 4 x 3 ) , ïî

if if

1 1 £x£ 2 2

1 £ x £1 2

if - 1 £ x £ -

æ 1ö

= cosec–1 ç x ÷ è ø

1 2

www.thinkiit.in

9

INVERSE TRIGONOMETIC Property XVIII :

3 cos–1 x =

1 ì -1 3 if £ x £ 1 ï cos ( 4x - 3 x ) , 2 ïï 1 1 -1 3 í 2p - cos ( 4 x - 3x ) , if - £ x £ 2 2 ï ï2p + cos -1( 4 x 3 - 3x ) , if - 1 £ x £ - 1 ïî 2

Property XIX :

3 tan–1 x =

ì æ 3 x - x3 ö ÷, ï tan-1ç ç 1 - 3x 2 ÷ ï è ø ï 3ö æ ï -1 3 x - x ÷ , í p + tan çç 2 ÷ ï è 1 - 3x ø ï 3ö æ ï- p + tan-1ç 3x - x ÷ , ç 1 - 3x2 ÷ ï è ø î

if -

1

if x >

0; a 3 ax 3 ø è

tan

æ x ç ç 2 2 è a -x

Thus, tan

–1

ö ÷ ÷ ø

= tan

–1

æ x ç ç 2 2 è a -x

ö ÷ ÷ ø

æ ö a sin q ç ÷ ç 2 2 2 ÷ è a - a sin q ø

tan

æ a sin q ö

æxö

æxö

= sin–1 ç a ÷ è ø

æ 3a 2 x - x 3 ö ç ÷ ç a3 - 3ax 2 ÷ è ø

= tan

–1

æ 3a3 tan q - a3 tan3 q ö ç ÷ ç a3 - 3a3 tan2 q ÷ è ø

= tan

–1

æ 3 tan q - tan3 q ö ç ÷ ç 1 - 3 tan2 q ÷ è ø

æxö

= tan–1 (tan 3q) = 3q = 3 tan–1 ç a ÷ è ø æ 3a3 x - x 3 ö æxö ÷ –1 ç ÷ Thus, tan–1 çç 3 2 ÷ = 3 tan a

è ø

è a - 3ax ø

Sol.

Simplify : æ a cosx - b sinx ö a ÷ , if tan x > –1 b cos x + a sin x b è ø

(i)

tan–1 ç

(ii)

tan

(i)

We have

tan

–1

1 2

æ 2x 1 - y2 ö ç sin -1 ÷ ,| x | < 1, y > 0 and xy < 1 + cos -1 2 ç 1+ x 1 + y 2 ÷ø è

æ a cos x - b sin x ö ç ÷ è b cos x + a sin x ø

= tan

–1

æ a cos x - b sin x ç b cos x ç ç b cos x + a sin x ç b cos x è

ö ÷ ÷ ÷ ÷ ø

= tan

–1

ö æ a ç - tan x ÷ ÷ ç b ç 1 + a tan x ÷ ÷ ç b ø è

æ p-q ö a = tan–1 çç 1 + pq ÷÷ , where p = and q = tan x b è ø æaö

æaö

= tan–1 p – tan–1 q = tan–1 ç b ÷ – tan–1 (tan x) = tan–1 ç b ÷ – x è ø è ø (ii)

3

= tan–1 ç a cos q ÷ = tan–1 (tan q) = q = sin–1 ç a ÷ è ø è ø

Let x = a tan q. Then –1

Ex.2

a

Let x = a sin q. Then, –1

(ii)

(ii) tan

–1

Let x = tan q and y = tan f. Then tan

2ö æ 1 ç sin -1 2x + cos -1 1 - y ÷ 2 1+ x 1 + y 2 ÷ø 2 çè

www.thinkiit.in

11

INVERSE TRIGONOMETIC æ 1 -1 2x 1 - y 2 ö÷ 1 ç sin + cos -1 ç2 1 + y 2 ÷ø 1+ x2 2 è

= tan

é ù -1 -1 = tan ê 2 (2 tan x ) + 2 [2 tan ( y)]ú ë û 1

1

tan q + tan f

x+y

= tan (tan–1 x + tan–1 y) = tan (q + f) = 1 - tan q tan f = 1 - xy Ex.3

Prove that (i) tan–1

Sol.

(i)

2 11

+ tan–1

= tan–1

2 11

+ tan

tan

tan

–1

1 2

7 24

= tan

–1

–1

1 7

1 2

+ tan–1

+ tan

Now, 2 tan–1

= tan–1

1 2

+ tan–1

1 2

+ tan–1

1 7

= tan–1

31 17

7 ö æ 2 + ÷ ç 11 24 ÷ ç ç 1- 2 ´ 7 ÷ ÷ ç è 11 24 ø

æ 125 ö 1 = tan–1 ç 250 ÷ = tan–1 2 è ø

= tan

–1

9 13

1 7

æ 1 1 ö + ÷ ç ç 2 7 ÷ ç 1- 1 ´ 1 ÷ ÷ ç 2 7ø è

= tan–1

= tan–1

1 2

æ 9 ö

= tan–1 ç 13 ÷ è ø æ

..............(1) 1ö

1

-1 -1 + ç tan 2 + tan 7 ÷

è

æ 1 9 ö + ÷ ç ç 2 13 ÷ ç 1- 1 ´ 9 ÷ ÷ ç 2 13 ø è

ø

æ 31 ö

= tan–1 ç 17 ÷ è ø

Find the value of : æ

2p ö

è

ø

æ

(i) sin–1 ç sin 3 ÷ Sol.

(ii) 2 tan–1

We have –1

Ex.4

1 2

We have –1

(ii)

7 24

(i)

(ii) tan–1 ç tan è

3p ö ÷ 4 ø

(iii)

We know that sin–1 (sin x) = x 2p ö

æ

\

2p sin–1 ç sin 3 ÷ = è ø 3

But,

2p 3

However,

p p

é ù Ï ê- 2 , 2 ú , which is the principal branch of sin–1 x ë û

2p ö é p pù æ 2p ö æ p p sin ç 3 ÷ = sin ç p - 3 ÷ = sin and Î ê- 2 , 2 ú ë û è ø è ø 3 3 2p ö

æ

p Hence, sin–1 ç sin 3 ÷ = è ø 3

(ii)

We know that tan–1 (tan x) = x 3p ö

æ

Þ

3p tan–1 ç tan 4 ÷ = è ø 4

But,

3p 4

æ

p pö

è

ø

Ï ç - 2 , 2 ÷ , which is the principal branch of tan–1 x

www.thinkiit.in

æ

cos–1 ç cos è

7p ö ÷ 6 ø

12

INVERSE TRIGONOMETIC However,

tan

æ pö

æ pö

æ

p pö

æ æ p öö = tan çç p + ç - ÷ ÷÷ = tan ç - 4 ÷ and ç - 4 ÷ Î ç - 2 , 2 ÷ è ø è ø è ø è 4 øø è

3p 4

3p ö æ p Hence, tan–1 ç tan 4 ÷ = – è ø 4

(iii)

We know that cos–1 (cos x) = x 7p ö

æ

Þ

7p cos–1 ç cos 6 ÷ = è ø 6

But,

7p 6

Ï [0, p] which is the principal branch of cos–1 x 5p ö æ 5p 5p = cos ç 2p - 6 ÷ = cos and Î (0, p) è ø 6 6

7p 6

However, cos

7p ö

æ

5p Hence, cos–1 ç cos 6 ÷ = è ø 6

Ex.5

Prove that æ 1+ x - 1- x ö 1 p 1 tan–1 çç 1 + x + 1 - x ÷÷ = – cos–1 x, for – £x£1 2 2 2 è ø

Sol.

Let x = cos 2 q. Then,

1+ x

= 1 + cos 2q = 2 cos2 q = 2 cos q

= 1 - cos 2q = 2 sin2 q = 2 sin q

and

1- x

\

æ 1+ x - 1 - x ö LHS = tan–1 çç 1 + x + 1 - x ÷÷ è ø æ 2 cos q - 2 sin q ö = tan–1 çç 2 cos q + 2 sin q ÷÷ = tan–1 è ø

æ cos q - sin q ö ç ÷ è cos q + sin q ø

æ 1 - tan q ö

= tan –1 ç 1 + tan q ÷ = tan –1 è ø

é æp öù êtanç - q ÷ú øû ë è4 p 4

= Ex.6

–q=

1 2

cos–1 (x) = RHS

æ 1- x ö 1 cos–1 ç 1+ x ÷ , 2 è ø

x Î (0, 1)

Let x = tan2 q. Then,

Further, RHS = Ex.7

Prove that tan–1 x =

Sol.

p 4

x

= tan q; and so tan–1 ( x ) = tan–1 (tan q) = q

1 2

cos

–1

æ 1- x ö ç ÷ è 1+ x ø

=

1 2

cos

–1

æ 1 - tan 2 q ö ç ÷ ç 1 + tan 2 q ÷ è ø

=

1 2

cos–1 (cos 2q) =

1 2

× 2q = q

Hence, LHS = RHS Solve each of the following for x : æ 8ö

æ 15 ö

p (i) sin–1 ç ÷ + sin–1 ç ÷ = 2 è xø è x ø

(ii) sin–1 (x) – cos–1 (x) = sin–1 (3x – 2), if x > 0 æ 8ö

(iii) tan–1 (x + 1) + tan–1 (x – 1) = tan–1 ç 31÷ è ø

(iv) tan–1 2x + tan–1 3x =

www.thinkiit.in

p 4

13 Sol.

INVERSE TRIGONOMETIC (i)

æ8ö

æ 15 ö

æ8ö

Þ

p sin–1 ç x ÷ = – sin–1 ç x ÷ è ø 2 è ø

Þ

15 x

æp -1 8 ö 8ö æ = sin ç 2 - sin x ÷ Þ = cos ç sin -1 ÷ è ø xø è

Þ

15 x

æ8ö = 1- ç ÷

Þ

(ii)

æ 15 ö

p We have sin–1 ç x ÷ + sin–1 ç x ÷ = è ø è ø 2

2

èxø

289 x2

225

Þ

x

Þ

=1

2

=1–

64 x2

x = ± 17

But, x = –17 cannot satisfy the given equation. \ x = 17 –1 Let sin x = a and cos–1 x = b. Then x = sin a and x = cos b Þ cos a = 1- x 2 = sin b From the given condition, we have a – b = sin–1 (3x – 2) Þ 3x – 2 = sin (a – b) = sin a cos b – cos a sin b Þ 3x – 2 = x2 – (1 – x2) Þ 3x – 2 = 2x2 – 1 Þ 2x2 – 3x + 1 = 0 Þ (2x – 1) (x – 1) = 0 Þ

(iii)

x = 1,

1 2

We have, tan–1 (x + 1) + tan–1 (x – 1) = tan–1

8 31

æ ( x + 1) + ( x - 1) ö 8 tan–1 çç 1 - ( x + 1)( x - 1) ÷÷ = tan–1 31 è ø

Þ

2x 1 - ( x 2 - 1)

=

8 , 31

assuming that (x + 1) (x – 1) < 1 i.e., x2 – 1 < 1

Þ

2x 2 - x2

=

8 31

Þ Þ Þ

62x = 16 – 8x2 8x2 + 62x – 16 = 0 4x2 + 31x – 8 = 0

Þ

x=

- 31 ± 961 + 128 8

i.e.,

=

- 31 ± 33 8

=

1 4

x2 < 2

or –8

When x = – 8, x2 = 64 1 So, we reject x = –1 and accept x = Ex.8

Solve for x : 2 tan–1 x = sin–1

Sol.

Let a = tan q and b = tan f. æ 2a ö ÷ 2÷ è 1+ a ø

Then, sin–1 çç

1 6

2a 1 - b2 –1 2 – cos 1+ a 1+ b2

æ 2 tan q ö ÷ 2 ÷ è 1 + tan q ø

= sin–1 çç

= sin–1 (sin 2q) = 2q and

cos

–1

æ 1 - b2 ö ç ÷ ç 1 + b2 ÷ è ø

= cos

–1

æ 1 - tan2 f ö ç ÷ ç 1 + tan2 f ÷ è ø

= cos–1 (cos 2f) = 2f Hence, RHS = 2q – 2f = 2 (q – f) = 2 (tan–1 a – tan–1 b) So, the given equation implies 2 tan–1 x = 2 (tan–1 a – tan–1 b), –1 < a < 1, –1 < b < 1 Þ tan–1 x = tan–1 a – tan–1 b æ a-b ö

= tan–1 ç 1 + ab ÷ ; ab > –1 è ø Þ Ex.9

Sol.

x=

a-b 1 + ab

; ab > –1

Solve : (i) 2 tan–1 (cos x) = tan–1 (2 cosec x) 1- x 1+ x

1 2

(ii)

tan–1

(iii) (i)

sin [2 cos–1 {cot (2 tan–1 x)}] = 0 We have 2 tan–1 (cos x) = tan–1 (2 cosec x) Þ Þ

=

tan–1 x (x > 0)

æ 2 cos x ö ÷ 2 ÷ è 1 - cos x ø

tan–1 çç

2 cos x 2

1 - cos x

=

æ 2 ö

= tan–1 ç sin x ÷ è ø

2 sin x

Þ sin x (cos x – sin x) = 0 when sin x = 0, x = np, n Î Z

Þ

sin x cos x = 1 – cos2 x = sin2 x

Þ

sin x = 0 or cos x – sin x = 0

www.thinkiit.in

15

INVERSE TRIGONOMETIC p 4

when cos x – sin x = 0 or tan x = 1, x = np + (ii)

We have, tan–1 Þ

1 2

=

tan–1 x 1 2

tan–1 1 – tan–1 x = p 4

Þ Þ (iii)

1- x 1+ x

= tan–1 x +

tan–1 x =

We have,

2 3

(x > 0)

1 2

tan–1 x =

p 4

=

×

p 6

=

1 3

é

ì

é

ëê

ïî

ë

–1

æ 2x ö ù üïù ÷÷ ú ýú è 1 - x 2 ø û ïþûú

=0

(Q 2 tan-1 x = tan–1

öüïù ÷ ýú 2x ÷øïú þû

=0

(Q cot–1 x = tan–1

é

ì

æ

ê ë

ïî

è

é

æ

êë

è 2x øúû

Þ

1- x ÷ ú sin ê2 cos-1çç ÷ =0

Þ

p 6

sin [2 cos {cot (2 tan x)}] = 0 –1

1- x sin ê2 cos-1ïícotçç cot -1

sin

2

2

2x 1- x2

1 ) x

é ì 2 üù æ 1 - x 2 ö ïú ê -1ï æç 1 - x 2 ö÷ ç ÷ 1êsin í2ç ÷ ç 2 x ÷ ýú ï è 2x ø ê è ø ïú þû î ë æ 1 - x2 ö ÷ 1- ç ç 2x ÷ è ø

=0

(Q 2 cos–1 x = sin–1 (2x 1- x 2 )]

2

=0

1- x2 x

Þ

= 0

or

2

Þ (1 – x2)2 = 4x2 Now,

)

öù

æ 1 - x2 ö ç ÷ ç x ÷ è ø

Þ

Þ

tan–1 x

Þ x = tan

Þ

Þ Þ Þ

3 2

(Q tan–1 1 + xy = tan–1 x – tan–1y)

sin ê2 cos-1ïícot êtan-1çç

Þ

æ 1 - x2 ö ÷ 1- ç ç 2x ÷ è ø

x-y

tan–1 x

=0

1 – x = 0 or 2

æ 1 - x2 ö ç ÷ ç 2x ÷ è ø

2

=1

Þ

x = ±1

(1 – x2)2 = 4x2 implies (1 – x2)2 – (2x)2 = 0 2 (1 – x – 2x) (1 – x2 + 2x) = 0 1 – x2 – 2x = 0 or 1 – x2 + 2x = 0 2 x + 2x – 1 = 0 or x2 – 2x – 1 = 0 x = –1 ± 2

or

x=1± 2

Hence, x = ±1, –1 ± 2 , 1 ± 2

www.thinkiit.in

or

16

INVERSE TRIGONOMETIC

UNSOLVED PROBLEMS EXERCISE – I Q.1

Evaluate the following :– (i)

Q.2

4p ö

æ

cos–1 ç cos 3 ÷ è ø

(ii)

cos–1 (cos 10)

(iii)

Prove that æ a-b ö

æ b-c ö

æ c -a ö

tan–1 ç 1 + ab ÷ + tan–1 ç 1 + bc ÷ + tan–1 ç 1 + ca ÷ è ø è ø è ø 3 ö 3 ö æ a3 - b3 ö æ 3 æ 3 ÷ + tan–1 ç b - c ÷ + tan–1 ç c - a ÷ = tan–1 çç 3 3÷ 3 3÷ 3 3÷ ç ç

è 1+ a b ø

Q.3

12 13

+ cos–1

4 5

+ tan–1

63 16

=p

Prove that æ

ö

x a-b 2 tan–1 çç a + b tan 2 ÷÷ = cos–1 è ø

Q.5

è 1+ c a ø

Prove that sin–1

Q.4

è 1+ b c ø

If tan–1x + tan–1y + tan–1z =

æ b + a cos x ö ç ÷ è a + b cos x ø

for 0 < b £ a and x ³ 0

p , prove that 2

xy + yz + zx = 1 Q.6

If cos–1x + cos–1y + cos–1z = p, prove that x2 + y2 + z2 + 2xyz = 1

Q.7

If sin–1x + sin–1y + sin–1z = p, prove that x 1- x 2 + y 1- y 2 + z 1- z 2 = 2xyz

Q.8

Solve : tan–1 2x + tan–1 3x =

Q.9

Solve : sin–1x + sin–1y =

p 4

2p 3

cos–1x – cos–1y =

p 3

Q.10

If sin [2 cos–1 {cot (2 tan–1 x)}] = 0, find x.

Q.11

If –1 £ x, y, z £ 1, such that sin–1x + sin–1y + sin–1z =

3p 2

,

find the value of x2000 + y2001 + z2002 –

9 x

2000

+y

2001

+ z 2002

www.thinkiit.in

é1æ

5 öù

tan ê çç cos-1 ÷÷ú 3 øúû êë 2 è

17 Q.12

INVERSE TRIGONOMETIC Prove that tan–1

Q.13

1 3

+ ........... + tan–1

æ n ö

1

= tan–1 ç n + 2 ÷ è ø n + n +1 2

Sum to n terms the series æ

ö x ÷ 2 ÷ . 1 + 1 2 x è ø

tan–1 çç

Q.14

1 7

+ tan–1

æ

æ

ö x ÷ 2 ÷ . 1 + 2 3 x è ø

ö x ÷ 2 ÷ . 1 + 3 4 x è ø

+ tan–1 çç

+ tan–1 çç

+...........

Establish the algebraic relation between x, y, z if tan–1x, tan–1y, tan–1z are in A.P. and if further x, y, z are also in A.P., their prove that x = y = z

Q.15

If tan–1x + tan–1y + tan–1z =

Q.16

Solve that equation for x ; 2x

3 sin–1

Q.17

and x + y + z = 3 , then prove that x = y = z

– 4 cos–1

1 - x2 1+ x

2

+ 2tan–1

2x 1- x2

=

p 3

If sin (p cos q) = cos(p sin q), prove that q=±

Q.18

1+ x

2

p 2

1 2

Prove that tan–1

sin–1

yz xr

3 4

zx

+ tan–1 yr + tan–1

xy zr

=

p , 2

where x2 + y2 + z2 = r2 Q.19

Prove that æ a1 x - y ö

æ a2 - a1 ö

æ a3 - a2 ö

æ an - an-1 ö

æ 1 ö

tan–1 çç a y + x ÷÷ + tan–1 çç a, a + 1 ÷÷ + tan–1 çç a a + 1÷÷ + .......+ tan–1 çç a a + 1 ÷÷ + tan–1 çç a ÷÷ = tan– è nø 2 ø ø è 1 è è n n-1 ø ø è 2 3 æxö ç y ÷÷ è ø

Q.20

If a1, a2, a3, .............. form an A.P. with common difference d (a > 0, d > 0) prove that d

d

d

a

-a

n+1 n tan–1 1 + a a + tan–1 1 + a a + .......... + tan–1 1 + a a = tan–1 1 + a a 1 2 2 3 n n+1 1 n+1

www.thinkiit.in

18

INVERSE TRIGONOMETIC

BOARD PROBLES EXERCISE – II æ 1ö

æ 1ö

æ 1ö

æ 1ö

Q1.

p Prove that following : tan–1 ç 3 ÷ + tan–1 ç 5 ÷ + tan–1 ç 7 ÷ + tan–1 ç 8 ÷ = . è ø è ø è ø è ø 4

Q2.

Using principal value, evaluate the following : cos–1 ç cos 3 ÷ + sin–1 ç sin 3 ÷ è ø è ø

2p ö

æ

æ

æ 1 + sin x + 1 - sin x ö æ pö x Prove the following : cos–1 çç 1 + sin x - 1 - sin x ÷÷ = , x Î ç 0, ÷ 2 è 4ø è ø OR Solve for x : 2 tan–1(cos x) = tan–1 (2 cosec x)

Q3.

æ

Q4.

Write the principal value of cos–1 ç cos

Q5.

Prove the following : tan–1 x + tan–1 çç

è

7p ö ÷ 6 ø

æ 2x ö ÷÷ è 1 - x2 ø

æ 3x - x 3 ö ÷ 2 ÷ è 1- 3x ø

1 + x2

[CBSE 2010]

2 + x2

4p ö ÷. 5 ø

[CBSE 2010 ]

Q6.

Find the value of sin–1 ç sin

Q7.

p 1 Prove that : tan–1 ê 1 + x + 1 - x ú = – cos–1 x, – êë úû 4 2

é 1+ x - 1- x ù

1 2

£x£1

6 æ -1 3 -1 3 ö Prove the following : cosç sin 5 + cot 2 ÷ = 5 13 è ø Show that :

Q8. Q9.

[CBSE 2009]

= tan–1 çç

Prove the following : cos [tan–1 (sin {cot–1 x)}] =

è

[CBSE 2008]

[CBSE 2009]

OR

æ

2p ö

[CBSE 2008]

[CBSE 2011] [C.B.S.E. 2012]

tan æç 1 sin-1 3 ö÷ = 4 - 7 è2

3

OR

Solve the following equation : 3ö 4ø

æ

cos(tan–1x) = sin ç cot -1 ÷ è

[C.B.S.E. 2013]

ANSWER KEY EXERICISE – 1 (UNSOLVED PROBLEMS) 1. (i)

2p 3

11. 0

æ3- 5 ö ÷ ÷ è 2 ø

8. x =

ö æ nx ÷ ç ç 1 + (n + 1)x 2 ÷ ø è

16. x = 3

(ii) (4p – 10) (iii) çç –1

13. S = tan

1 6

9. x =

1 , y= 1 2

1

EXERICISE – 2 (BOARD PROBLEMS) Q2. p

Q3.

p 4

Q4.

5p 6

Q6.

p 5

www.thinkiit.in

10. x = ±1, ± (1 ± 2 )